DEVELOPING SUPPLEMENTARY TEACHING SPEAKING MATERIALS BASED ON COMMUNICATIVE LANGUAGE TEACHINGFOR SECOND YEAR STUDENTS OF SENIOR HIGH SCHOOL AT AN-NUR ISLAMIC BOARDING SCHOOL OF MALANG, EAST JAVA, INDONESIA - Dedi Efrizal (Linguists : Journal of Linguistics and Language Teaching, 2015)
Almost of second year students of senior high school at An-Nur Islamic boarding school of Malang, East Java, encountered many problems in speaking activity. The main problem was there were not appropriate teaching English speaking materials that give big portion and opportunity for the students to speak actively and freely in order to support teaching and learning process of English speaking. Concerning these problems, a set of supplementary teaching English speaking materials for the students based Communicative Language Teaching needed to be developed. In this research, the researcher employed the procedures: conducting need assessment, developing supplementary materials, conducting expert validation, revising the materials, trying out the materials, and revising the materials. The researcher collected the data by using questionnaires, interview, analyzing the syllabus, and note field. The product of this research is seven units of supplementary teaching English speaking materials for second year students of senior high school at An-Nur Islamic boarding school of Malang, East Java.